Moral hazard among the sick and unemployed: Evidence from a Swedish social insurance reform - Laura Larsson; Caroline Runeson (Institute for Labour Market Policy Evaluation (IFAU), 2007)
This paper looks at a specific type of moral hazard that arises in the interplay between two large public insurance systems in Sweden, namely the sickness insurance (SI) and the unemployment insurance (UI). Moral hazard can arise from the benefit size structure as for some unemployed persons, benefits from the SI are higher than benefits from the UI. We use a reform of the SI system that came in force 1 July, 2003, to identify the effect of economic incentives arising from the different benefit sizes. Our results from a duration analysis show clearly that the higher the benefits, the larger the probability of reporting sick.
Keywords: C41; H55; I18; J64; J65; 330; Unemployment insurance; sickness insurance; health; duration analysis; discrete hazard models; Arbeitslosenversicherung; Gesetzliche Krankenversicherung; Moral Hazard; Statistische Bestandsanalyse; Schweden